Organic carbon stocks in Mediterranean soil types under different land uses (Southern Spain) - Munoz-Rojas, Miriam; Jordan, A.; Zavala, L.; De La Rosa, D.; Abd-Elmabod, S.; Anaya-Romero, M. (2012)
Soil C sequestration through changes in land use and management is one of the sustainable and long-term strategies to mitigate climate change. This research explores and quantifies the role of soil and land use as determinants of the ability of soils to store C along Mediterranean systems. Detailed studies of soil organic C (SOC) dynamics are necessary in order to identify factors determining fluctuations and intensity of changes. In this study, SOC contents from different soil and land use types have been investigated in Andalusia (Southern Spain). We have used soil information from different databases, as well as land use digital maps, climate databases and digital elevation models. The average SOC content for each soil control section (0-25, 25-50 and 50-75 cm) was determined and SOC stocks were calculated for each combination of soil and land use type, using soil and land cover maps. The total organic C stocks in soils of Andalusia is 415 Tg for the upper 75cm, with average values ranging from 15.9 Mg C ha-1 (Solonchaks under "arable land") to 107.6 Mg Cha-1 (Fluvisols from "wetlands"). Up to 55 % of SOC accumulates in the top 25 cm of soil (229.7 Tg). This research constitutes a preliminary assessment for modelling SOC stock under scenarios of land use and climate change. © Author(s) 2012. CC Attribution 3.0 License.